The Politics of John W. Dafoe and the Free Press - Cook, Ramsay (Book collections on Project MUSE., 1963)
This book is a study at close quarters of Dafoe, the man of politics. It is the biography of a political mind. The impression is of a mind recalled to its full vigour, for no prejudgments have been made about it and no restraints upon it.